Analysis on the relationship among green finance, government environmental governance and green economic efficiency: evidence from China - Wu, Yangyulong (Frontiers in Environmental Science, 2024)
Investigating the relationship between green finance (GF), government environmental governance (GEG), and green economic efficiency (GEE) is essential for developing sustainable development policies. This study uses panel data from 30 provincial administrative regions in China, covering the period from 2011 to 2021, to assess the effects of GF and GEG on GEE through the Spatial Durbin Model. The findings reveal several key points. First, most provinces are in low-low spatial clusters in terms of GEE, though there is a gradual improvement over time. Second, GF significantly enhances GEE, while GEG has a notable inhibitory effect. Third, GF exhibits a positive spatial spillover effect on the GEE of neighboring regions, whereas GEG shows a negative spatial spillover effect. Fourth, these spillover effects are mainly observed in the eastern regions, with little significance in the central and western areas. Moreover, one of the GEG indicators, environmental regulation, demonstrates a positive spatial spillover effect in the eastern region, contrary to the overall negative national trend. In general, this paper examines the interplay among the three variables within a unified analytical framework, filling the gaps in existing research. Furthermore, the paper delineates GEG into environmental regulation and environmental investment, which is a dimension frequently neglected in current research.